On a Fast Integral Equation Method for Diffraction Gratings (Communications in Computational Physics, 2020)
The integral equation method for the simulation of the diffraction by optical gratings is an efficient numerical tool if profile gratings determined by simple cross-section curves are considered. This method in its recent version is capable to tackleprofile curves with corners, gratings with thin coated layers, and diffraction scenarioswith unfavorably large ratio period over wavelength. We discuss special implementational issues including the efficient evaluation of the quasi-periodic Green kernels,the quadrature algorithm, and the iterative solution of the arising systems of linearequations. Finally, as an example we present the simulation of echelle gratings whichdemonstrates the efficiency of our approach.